Understanding of the concept “Use of vehicles” in the EU motor insurance - Ivanova, Anna (Riga Graduate School of Law, 2018)
The major objective of the thesis is identifying the meaning of the concept “use of vehicles” firstly adopted under Article 3(1) of First MID (Directive 72/166/EEC). The main research question of the thesis is whether the concept “use of vehicles” should be understood broadly or narrowly and whether such interpretation may lead to different outcomes in national practices among the EU Member States.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; Insurance law